Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1063/1.3267144
|View full text |Cite
|
Sign up to set email alerts
|

Hot electron effect in nanoscopically thin photovoltaic junctions

Abstract: The open circuit voltage in ultrathin amorphous silicon solar cells is found to increase with light energy ͑frequency͒, due to extraction of hot electrons. The ultrathin nature of these junctions also leads to large internal electric fields, yielding reduced recombination and increased current. A simple phenomenological argument provides a qualitative understanding of these effects and gives guidelines for designing future, high-efficiency, hot electron solar cells. A J sc [I-V] J sc [EQE] P/P(60 nm) J sc (mA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 16 publications
3
35
0
Order By: Relevance
“…The ultrathin active layer of 30 nm of our absorber structure may seem too thin to form a p-i-n junction. However, an a-Si solar cell of a 20 nm thick p-i-n (5 nm-10 nm-5 nm) junction has been experimentally demonstrated and it has been reported that the ultrathin nature of these junctions can lead to large internal electric fields, yielding reduced recombination and increased current [24].…”
Section: Application To Solar Cellsmentioning
confidence: 99%
“…The ultrathin active layer of 30 nm of our absorber structure may seem too thin to form a p-i-n junction. However, an a-Si solar cell of a 20 nm thick p-i-n (5 nm-10 nm-5 nm) junction has been experimentally demonstrated and it has been reported that the ultrathin nature of these junctions can lead to large internal electric fields, yielding reduced recombination and increased current [24].…”
Section: Application To Solar Cellsmentioning
confidence: 99%
“…All this reduces conversion efficiency of solar cells. Recently it was shown [3] that the extraction of hot electrons increases the open circuit voltage in ultrathin α-Si p-i-n solar cells. To observe the increase of the open circuit voltage the thickness of the solar cells must be less than 25 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical work by Kempa shows that hot electrons generated in a semiconductor [52] can couple their excess free energy into an adjacent metal surface in the form of SPPs [53]. By comparing electron-phonon and electron-plasmon coupling probability amplitudes, he concluded that hot electrons are more probable to couple to surface plasmons.…”
Section: Hot Electron Couplingmentioning
confidence: 99%